2018
DOI: 10.3390/su10113937
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Conventional and Innovative- Sustainable Methods for Cleaning Reflectors in Concentrating Solar Power Plants

Abstract: The severe soiling of reflectors deployed in arid and semi arid locations decreases their reflectance and drives down the yield of the concentrating solar power (CSP) plants. To alleviate this issue, various sets of methods are available. The operation and maintenance (O&M) staff should opt for sustainable cleaning methods that are safe and environmentally friendly. To restore high reflectance, the cleaning vehicles of CSP plants must adapt to the constraints of each technology and to the layout of reflect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 48 publications
(27 citation statements)
references
References 44 publications
0
27
0
Order By: Relevance
“…However, they have proved difficult to translate to the field, where harsh conditions interfere with the electronic systems, and dust becomes cemented to the surface by moisture. 2,45,47,85 Some common issues have been reported, including reduced effectiveness in cases of high relative humidity, 2,89 long particle duration on the surface, 2,85 and low surface tilt angle. 89 A recently launched commercial device reported 32% soiling rate reduction in Saudi Arabia, 87 but large-scale implementation has not occurred yet due to its relatively high cost of around 30 V/m 2 (PV module prices are actually in the range of 30-90 V/m 2 ).…”
Section: Electrodynamic Screensmentioning
confidence: 99%
See 1 more Smart Citation
“…However, they have proved difficult to translate to the field, where harsh conditions interfere with the electronic systems, and dust becomes cemented to the surface by moisture. 2,45,47,85 Some common issues have been reported, including reduced effectiveness in cases of high relative humidity, 2,89 long particle duration on the surface, 2,85 and low surface tilt angle. 89 A recently launched commercial device reported 32% soiling rate reduction in Saudi Arabia, 87 but large-scale implementation has not occurred yet due to its relatively high cost of around 30 V/m 2 (PV module prices are actually in the range of 30-90 V/m 2 ).…”
Section: Electrodynamic Screensmentioning
confidence: 99%
“…93 Site Selection, Adaption, and Monitoring The possibility of soiling mitigation through selection and modification of the plant site has received little attention from PV researchers. However, lessons can be drawn from experience with CSP systems, 45 which are more strongly affected by soiling than PV. First, soiling (daily loss rate, rain frequency, and dust characteristics) should be analyzed at each potential site during resource assessment measurement campaigns using full-size PV modules or CSP soiling measurement devices at their intended tilt or tracking pattern and orientation.…”
Section: Pv Module Designmentioning
confidence: 99%
“…This system can spare huge amounts of water, and therefore, lead to a decrease in task and support cost. In any case, it must be viewed as that the system relies upon the dew potential of the Concentrated Solar Power (CSP) plant area, which is exemplarily researched for one solar site [8]. Other studies showed that dust gets accumulated on the front surface of the module and blocks the incident light from the sun.…”
Section: Introductionmentioning
confidence: 99%
“…Said et al [11] presented a review of the effect of climatic conditions on the performance of PV modules, particularly the soiling issue, where they reviewed the past, current, and future approaches for mitigating the effect of dust in that regard. Many other studies in that regard can be found examining self-cleaning coating solutions and their durability (passive dust mitigation techniques) and mechanical cleaning as well (active dust mitigation techniques) [12][13][14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%